К вопросу о „посредничестве” русской литературы в развитии польско-грузинских литературных связей - Occheli, Wiera (Acta Polono-Ruthenica, 2018)
The article describes one of the types of the literary „mediation” - the mediator-story, presented from the history of Polish-Georgian literary relations of XIX century. It is shown that the stories of the Russian historian and writer E.P. Karnovich Stanislaw August, King of Poland and Panna Elzbieta, reflecting the individual episodes in the history of Poland and translated into Georgian, played the role of „mediator” in familiarizing Georgian reader with the details of the life and work of the last Polish king Stanislaw August Poniatowski II. The study also gives the reason to believe that the stories of Russian writer gave the opportunity to see the similarity of some stages of the historical development of Poland and Georgia, and the proximity of the role played in the destiny of their country last Polish king Stanislaw August Poniatowski II and the last king of Georgia Giorgi Bagrationi XII.